Relación entre diámetro y la altura de dos especies forestales de las familias Anacardiaceae y Sapotaceae del arboretum "El Huayo" del CIEFOR Puerto Almendra, Loreto, 2021 - Talexio López, Gian Carlos (2022)
The study was carried out at the "El Huayo" Arboretum of CIEFOR Puerto Almendra - FCF - UNAP, San Juan Bautista district, Maynas province, Loreto region. The objective was to define the height-diameter relationship in two forest species of the botanical families Anacardiaceae and Sapotaceae. The variables used for the relationship were diameter and commercial height of the evaluated plants. The results indicate that for the commercial diameter-height relationship in the plants of Ecclinusa lanceolata (Mart. & Eichl.) Pierre "quinilla blanca" and Pouteria guianensis Aublet "quinilla" of the family Sapotaceae and Tapirira guianensis Aublet "huira caspi" and Tapirira retusa Ducke “huira caspi Hoja grande” of the Anacardiaceae family, the allometric model with the best fit was power; In addition, in both families an excellent degree of relationship was observed between the variables evaluated. Likewise, for the predictions, the equation of the allometric power model will be applied for the four species evaluated in natural forest.